When I receive ARVs through my group, my heart settles’: Participants’ perceptions and experiences of Friends for Life Circles for Option B+ in Kampala and Mityana Districts, Uganda - Rujumba, Joseph; King, Rachel L; Namale-Matovu, Joyce; Wavamunno, Priscilla; Amone, Alexander; Gabagaya, Grace; Rukundo, Gordon; Fowler, Mary Glenn; Homsy, Jaco; Seeley, Janet; Musoke, Philippa (Public Library of Science, 2023)
Abstract The Friends for Life Circles (FLC) was a parallel randomized controlled trial testing the efficacy of a group peer support intervention to support long-term adherence to Option B+ in Kampala and Mityana districts in Uganda. We explored FLC participants’ experiences and perceptions of the intervention on adherence to Option B+ for PMTCT and potential implications for strengthening the PMTCT program. We collected data from six focus group discussions with lactating women enrolled in the FLC intervention, and from 14 key informant interviews with health workers, district and national level stakeholders, as well as male partners of FLC participants. Data were analysed using a content thematic approach in a continuous and iterative process. Women described the FLC intervention as acceptable and beneficial in enhancing their understanding of HIV and the need for ART. The FLC helped women, especially those newly diagnosed with HIV infection to come to terms with their diagnosis and overcome the fear of death linked to testing HIV positive, and provided opportunities to enhance ART initiation, resumption and adherence. The FLC provided safe spaces for women, to learn about ART, and to receive support from peers including adherence reminders through home visits and ‘coded’ reminder messages. Receiving ART from support groups protected members from stigma and long lines at health facilities. Fear of stigma, health system challenges, the high cost of caring for animals and lack of money to save in groups were key challenges noted. The FLC support groups were crucial in providing needed support for women to initiate, resume and adhere to lifelong ART for Option B+. It is important that women who test HIV positive and start ART for life receive psychosocial support from peers and health workers to improve chances of preventing HIV transmission from mothers to children.
Keywords: HIV, HIV diagnosis and management, Health care facilities, Socioeconomic aspects of health, Antiretroviral therapy, Pregnancy, HIV prevention, Public and occupational